HUBUNGAN KECERDASAN NATURALIS DAN SIKAP PEDULI LINGKUNGAN SISWA KELAS TINGGI SD NEGERI 30 MICO - Sudarto, Sudarto; Achmad Shabir ,; Andi Lisa Mulawarman , (Jurnal Cakrawala Ilmiah, 2024)
This research is a correlation research that aims to determine whether there is or there is not a correlation between the students' naturalist intelligence and the environmental care attitude of the Students High Grade at SD Negeri 30 Mico, Palakka District, Bone Regency. The population of this research was all the high grade students, while the sample was the entire of the population, in totaling of 66 peoples. The sampling technique used was the saturated sampling technique. Research data was obtained using a questionnaire with the Guttman scale. The data analysis techniques used were descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis, naturalist intelligence obtained an average value of 19.42 and the attitude of caring for the environment obtained an average value of 18.50. Based on inferential statistical analysis, it showed that tcount (3.472) is greater than the ttable value (1.671). Thus, H0 was rejected and H1 was accepted, so it can be concluded that there is a significant correlation between naturalist intelligence and the environmental care attitude of high grade students at SD Negeri 30 Mico, Palakka District, Bone Regency